2019
DOI: 10.3390/molecules24112187
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Regioselective Synthesis of Benzofurans from Phenols and α-Haloketones

Abstract: Reported here is the direct synthesis of naphthofurans and benzofurans from readily available phenols and α-haloketones promoted by titanium tetrachloride which combines Friedel–Crafts-like alkylation and intramolecular cyclodehydration into one step. This simple protocol allows for the formation of a variety of high value naphthofurans and benzofurans within which a series of cyclic and acyclic groups are readily incorporated. This process demonstrates the advantages of high levels of regioselectivity, broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…And it was found that derivatives with aryl-and vinylic-substituted alkynes gave cyclization products in exceptional yields. [33] A one-pot reaction including Sonogashira coupling of dichlorophenols (21) phenylphosphine catalyst. [34] The general schematic representation of all the reactions mentioned above is shown in Figure 4.…”
Section: Chemistry Of Benzofuransmentioning
confidence: 99%
See 1 more Smart Citation
“…And it was found that derivatives with aryl-and vinylic-substituted alkynes gave cyclization products in exceptional yields. [33] A one-pot reaction including Sonogashira coupling of dichlorophenols (21) phenylphosphine catalyst. [34] The general schematic representation of all the reactions mentioned above is shown in Figure 4.…”
Section: Chemistry Of Benzofuransmentioning
confidence: 99%
“…[19] Synthetic analogs of benzofuran scaffold have been synthesized and many drugs bearing this moiety are available in the market treating various diseases, a few of which are given in Figure 2. [20,21]…”
Section: Introductionmentioning
confidence: 99%
“…One-pot processes for the synthesis of benzo[b]furans from aryl-or alkylketones using nonprecious Fe and Cu catalysis have been described by Sutherland and co-workers in 2020 (Scheme 32B and C) [165]. Benzofurans are important scaffolds present in several bioactive compounds, such as balsaminone A (91, antipruritic activity), xylarianaphthol-1 (92, anticancer activity), and amiodarone (93, antiarrhythmic activity) (Scheme 32A) [166]. The method consists of a tandem, regioselective Fe(III)-catalyzed C-H halogenation, followed by an Fe or Cu-catalyzed O-arylation to access the benzo[b]furan derivatives in high yields.…”
Section: Iron-catalyzed C-h Activationmentioning
confidence: 99%
“…More often, basic conditions are employed to improve the reactivity of naphthol as double nucleophile, as, for instance, in the classical approach of the annulation of 2-naphthol with dihalo compounds [ 18 ]. However, the use of p -TSA [ 19 , 20 ] or of metal catalysis [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] has also been pursued.…”
Section: Introductionmentioning
confidence: 99%